Analysis of Effective Communication Between Interview Officers and Passport Applicants - Suwardi M; Andi Vita Sukmarini; Mujahid Yunus (Journal La Sociale, 2026)
This study aimed to examine effective communication and the obstacles to building effective communication between interview officers and passport applicants at the Makassar Class I Special Immigration Office. It used a qualitative approach and involved 10 informants, consisting of 6 passport applicants and 4 photo and interview officers. Data were collected through interviews and analyzed using data reduction, data display, triangulation, and conclusion drawing and verification. The findings show that effective communication during the passport interview process was reflected in several practices. Officers delivered questions clearly, in detail, coherently, and in a friendly manner. They were also highly informative and applied the 5S principles, namely smile, greet, say hello, polite, and courteous. In addition, officers explained the legal basis and passport processing procedures according to standard operating procedures, while also educating applicants about passport storage and its functions. Effective communication was further seen in the provision of clear explanations regarding the basis of interview questions and in the officers’ ability to build understanding, influence emotions positively, and encourage good attitudes through clear, simple, and friendly language. The study also found several obstacles to effective communication, including applicants who were not accustomed to speaking Indonesian, differences in regional languages, limited public knowledge about immigration, the use of formal and unfamiliar immigration terms, insufficient information about passport requirements, differences in applicant backgrounds, and limited understanding of the passport application process.